Influência do estresse nutricional na severidade do déficit hídrico em plantas de pinhão manso - (:unkn) unknown (Universidade Estadual de Goiás, 2014)
Given the better understanding of the physiological fluid and nutritional deficiency occurring simultaneously, the objective of this study was to evaluate the implication of nitrogen fertilization on water stress in plants of Jatropha. The study was conducted in five gallon pots on benches in full sun, the State University of Goias, Unit Ipameri, Goias. The experiment was conducted following the completely randomized design in factorial arrangement 5 x 2 [(five urea rates (0; 1,2; 2,4; 3,6; 4,8g of urea per pot and two levels of water supply: irrigated and non-irrigated)] and five replications. Jatropha seeds were sown in pots containing 5L substrate composed of Oxisol Red-Yellow, sand and manure in the proportion of 3: 1: 0,5, respectively. At the time of nitrogen fertilization (10 days after germination ), each pot received 1,2g of Single Super Phosphate and 2,4g of Potassium Chloride as a source of P2O5 and K2O respectively. At 60 days after germination, half of the plants were subjected to 7 days of water deficit, and the other half was irrigated daily. On the 7th day without irrigation, plants were analyzed and then rehydrated for five days when they were again analyzed. After 67 and 72 days after germination, the following analyzes were made: number of leaves, plant height, branch diameter, sweating, relative water content, leaf area, total chlorophyll, root mass ratio, stem mass ratio, leaf mass ratio, aerial part / root system ratio, and total biomass. The nitrogen used in fertilizers and the availability of this nutrient for soil organic matter contributed to the lack of interaction between the factors water deficit and nitrogen. In water stress conditions, plants of jatropha have reduced vegetative growth and increased biomass partitioning to the root system. Jatropha plants are drought tolerant and have a strategy to delay dehydration.
Keywords: Nitrogênio; Seca; Produção vegetal; Nitrogen; Drought; Plant production; CIENCIAS AGRARIAS